Cystatin C as a biomarker for estimating glomerular filtration rate. Issue 3 (May 2015) - Ferguson, Thomas W.; Komenda, Paul; Tangri, Navdeep
<x xml:space="preserve">Abstract</x> Purpose of review Glomerular filtration rate (GFR) is rarely measured in clinical practice because of the complexity of the measurement. As such, kidney function is typically estimated using validated study equations, which use readily available data including age, sex, race, and serum creatinine as filtration marker. Contemporary research suggests that cystatin C may be an improved alternative to creatinine for inclusion in GFR estimating equations. The purpose of this article is to evaluate the benefits and limitations of using cystatin C as a biomarker of filtration. Recent findings Cystatin C has fewer non-GFR determinants, when compared with serum creatinine. Use of serum cystatin C avoids the limitations related to both diet and muscle mass that affect serum creatinine. Cystatin C may be more accurate than serum creatinine in estimating GFR, and is more strongly associated with all-cause mortality and cardiovascular events. Summary Cystatin C has some advantages over serum creatinine in estimating GFR. The use of cystatin C as a confirmatory biomarker in deciding medication dosages or as a confirmatory test in patients with an uncertain diagnosis of chronic kidney disease may be beneficial.